Improving the strength of sutureless laser‐assisted vessel repair using preloaded longitudinal compression on tissue edge. Issue 5 (27th January 2017) - Nakadate, Ryu; Omori, Shigeru; Ikeda, Tetsuo; Akahoshi, Tomohiko; Oguri, Susumu; Arata, Jumpei; Onogi, Shinya; Hashizume, Makoto
Abstract : Background and Objective: Little is known about the approximation of coapted edges in sutureless laser‐assisted vessel welding. Tissue shrinkage by laser irradiation may cause coapted edges to separate, reducing strength of welding. This may be avoided by preloaded longitudinal compression on the tissue edges to be welded. This study compared welding strength with and without preloaded compression in ex vivo animal experiments. Materials and Methods: This study evaluated 24 samples of harvested porcine carotid arteries, each having a length of 3 cm and an inner diameter of 1.0–2.0 mm. A half circumferential incision was made at the center of each sample. A steel shaft 2.0 mm in diameter was inserted into each sample to approximate the incised edges. The samples were longitudinally compressed to 6 mm. Incision sites were repaired by irradiation with a 970‐nm diode laser. No glue or die was used. The repair strength was evaluated by measuring the bursting point (BP) of all samples. In a pilot study, the welding conditions, including power, duration, and interval of the laser spots, were tested by trial and error in 18 samples, including six treated under optimum conditions. As a control group, six samples were welded under optimum conditions, but without compression. Results: Optimum conditions, consisting of 2.4 W power, 30‐second duration, and 1‐mm intervals of laser spots, yielded the highest BP (623 ± 236 mmHg), which was significantly higher than in the control group without compression (204 ± 208 mmHg, P = 0.009). Defining BP > 400 mmHg as successful repair, the success rates in the compression and control groups were 83% and 17%, respectively. Conclusion: Preloaded longitudinal compression on the coapted edges may be important for sutureless laser‐assisted vessel repair and anastomosis and may affect the strength of welding. Lasers Surg. Med. 49:533–538, 2017. © 2017 Wiley Periodicals, Inc.